Unveiling the metric structure of internal representations of space - Stella, Federico; Cerasti, Erika; Treves, Alessandro (Frontiers in Neural Circuits, 2013)
How are neuronal representations of space organized in the hippocampus? The self-organization of such representations, thought to be driven in the CA3 network by the strong randomizing input from the Dentate Gyrus, appears to run against preserving the topology and even less the exact metricity of physical space. We present a to assess this issue quantitatively, and find that in a simple neural network model of CA3, the average topology is largely preserved, but the local metricity only to a very limited extent.